Simulation of running impact using a viscoelastic model considering contact phase - Sakurai, Y.; Maruyama, T. (Procedia Engineering, 2010)
The purposes of this study were to develop and validate a new viscoelastic model which can consider the contact phases of running. For these purposes, a simple mechanical model of the human body including two contact points was developed. Three healthy male performed barefoot running at different speeds. The simulated values during the passive phase using this model were well estimated. It was shown that this new model may be useful to analyze the impact force during running.